The Grammatical Error Analysis in English Conversation of the Eleventh-Grade Students of Senior High School Level - Chamelya Vivi Crystanty Sene (Journal on Education, 2023)
The following questions are the focus of this research article: What kinds of grammatical errors do students in the eleventh grade make in their conversations? And which kind of grammar error do eleventh graders make the most frequently in their conversations? To answer those questions, the writer used a descriptive method. The subjects of this study were eleventh grade students. In collecting the data, the writer used conversation, and the topics were “meeting a new friend," “an invitation to a party," and “an invitation to watch a film." And “Idioms” The writer recorded each student as they performed the conversation they had selected. The analysis's conclusion demonstrates that (1) the kinds of errors committed by the students are: omission 8 made by 5 students, addition 1 made by 1 student, misformation 5 made by 4 students, and misordering 2 made by 2 students. And (2) The most common type of grammatical error committed by the students is omission 8. Based on the results of the research, the suggestions are as follows: (1) More grammar should be taught to the students, particularly the grammatical aspect. (2) By assigning exercises and practicing grammatical concepts, especially tenses, English teachers can help students with their grammatical errors.